Effect of dietary new sugar cane extract on growth performance and intestinal histology in broiler chickens - Khonyoung, Duddoa; Yamauchi, Koh-en; Sittiya, Janjira; Wonnakum, Pichit (Agriculture and Natural Resources, 2019)
The effects were investigated of feeding dietary new sugarcane extract (SCE) on the growth performance and intestinal histology of broiler chicks using two treatments and four replicates in a completely randomized design. Thirty-two newly hatched male broilers (Marshall Chunky) were assigned randomly to the two treatments: a basal diet group (control) and a basal diet supplemented with 0.1% new SCE group. There were no significant differences between the two treatment groups in feed intake, body weight gain and feed efficiency. Compared with the control, the broilers fed new SCE tended to increase in carcass percentage. Bird mortality was two in the control, and one in the new SCE group. There were no significant differences between groups regarding villus height, villus area and crypt depth in all intestinal segments, excepting the ileal villus height which tended to increase in the 0.1% new SCE group. Protuberated cells were observed on the jejunal and ileal villus apical surface in the 0.1% new SCE group. These results demonstrated that 0.1% dietary new SCE can activate intestinal epithelial cell function, especially in the jejunum and ileum segments.